مبدأ المشاركة بوصفه ضمانة لحماية الاستقلال الذاتي لولايات الدولة الاتحادية ( دراسة مقارنة ) - يونس مها بهجت; عاجب رائد حمدان (Journal of Legal Sciences, 2019)
The federal system of the components of the federal state provides autonomy to ensure a presence of its own constitution, independent and local authorities for the federal government. Also it saves a lot of disciplines especially as fall in internal affairs. This independence is an essential element in the presence of the federal state, so states keep to protect it in different ways. From the most important to ensure the participation of the Federal territorial units in the exercise of power, where reserves the right to representation in the composition of the federal bodies and contribute to their decisions.